Elevated circulating vascular cell Adhesion Molecule-1 (sVCAM-1) is associated with concurrent depressive symptoms and cerebral white matter Hyperintensities in older adults. Issue 1 (December 2015) - Tchalla, Achille; Wellenius, Gregory; Sorond, Farzaneh; Travison, Thomas; Dantoine, Thierry; Lipsitz, Lewis
Abstract Background Circulating vascular adhesion molecule-1 (sVCAM-1) is a presumed marker of endothelial activation and dysfunction, but little is known about its association with mood. We hypothesized that elevated plasma concentrations of sVCAM-1 may be a marker of depressive symptoms due to cerebral vascular disease. Methods We studied 680 community-dwelling participants in the MOBILIZE Boston Study, aged 65 years and older. sICAM-1 and sVCAM-1 were measured by ELISA assay and depressive symptoms were assessed during home interviews using the Revised Center for Epidemiological Studies Depression Scale (CESD-R). Cerebral White Matter Hyperintensities (WMHs) were quantified by MRI in a subgroup of 25 participants. Results One hundred seventy nine (27 %) subjects had a CESD-R Score ≥ 16, indicative of depressive symptoms. The mean sVCAM-1 concentration (±SD) was 1176 ± 417 ng/mL in a group with CESD-R Scores <16 and 1239 ± 451 ng/mL in those with CESD-R Scores ≥16 (p = 0.036). CESD-R Score was positively associated with sVCAM-1 (r = 0.11, p = 0.004). The highest quintile of sVCAM-1, which is indicative of endothelial dysfunction, was significantly associated with depressive symptoms compared to the lowest quintile (OR = 1.97 (1.14-3.57) p = 0.015). In a subset of subjects, sVCAM-1 concentration was positively correlated with cerebral WMHs volume (p = 0.018). Conclusions The association between high levels of sVCAM-1 and depressive symptoms may be due to endothelial dysfunction from cerebral microvascular damage. Future longitudinal studies are needed to determine whether sVCAM-1 can serve as a biomarker for cerebrovascular causes of depression.